Rol de la Microglía en el desarrollo del Glioblastoma (2024)
Glioblastoma multiforme is one of the most aggressive brain cancers, with an average survival of less than 15 months. Its high proliferation, invasion and suppression capacity immune make it resistant to chemotherapy, radiotherapy and surgery. what drives development of new therapies. A key factor in its lethality is its tumor microenvironment, which is consisting mainly of the tumor and microglia. Microglia are exclusive macrophages of the central nervous system which serves as the main defender against an infection or signs of damage, through phagocytosis and pro-inflammatory or anti-inflammatory mechanisms depending on the severity and status of the infection or injury.